Effect of Different Foliar Silicon Sources on Cotton Plants - de Souza Junior, Jonas Pereira [UNESP]; de Mello Prado, Renato [UNESP]; Soares, Mariana Bomfim [UNESP]; da Silva, José Lucas Farias [UNESP]; de Farias Guedes, Victor Hugo [UNESP]; dos Santos Sarah, Marcilene Machado [UNESP]; Cazetta, Jairo Osvaldo [UNESP] (Springer Nature, 2021)
The aim was to determine the source and concentration of Si that results in greater accumulation of this element, thereby improving the physiological variables and dry matter production of cotton plants. The experiment was conducted in a greenhouse using a randomized block design in a 4 × 4 factorial scheme consisting of four silicon sources: sodium and potassium silicate stabilized with sorbitol (SiAl), monosilicic acid stabilized with PEG400 (SiAc); nanosilica (Nano), and potassium silicate without stabilizers (SiK); and four silicon concentration (0.0; 0.3; 0.6; and 0.8 g L−1), in four repetitions. Leaf Si was supplied in four phenological stages. With a view to determining the homogeneity of the spray solution with Si in the sources used, the solution underwent a polymerization test. The boll and the shoot of the plants were collected, washed, dried, and weighed, and the shoot samples were ground to analyze Si content. Foliar spraying of Si is agronomically viable for the cotton plant since it increases Si accumulation, pigment production and quantum efficiency of photosystem II, and decreased initial and maximum fluorescence, favoring the production of dry matter and boll + seeds. Silicon in the form of sodium and potassium silicate stabilized with sorbitol performed best at a concentration of 0.8 g L−1 of Si in comparison with other sources studied.
Keywords: Beneficial element; Gossypium hirsutum; Leaf fertilization; Photosynthesis; Soluble source of silicon